Availability Of Human Capital Dimensions In The Banking Sector (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aims to determine the availability of the dimensions of human capital: knowledge, experience, skills and capabilities in the branches of private commercial banks in the Syrian coast.The research depended on the descriptive approach, and the research community included all officials (director, assistant director, head of department, head of a division or department) at the branches of private commercial banks in the Syrian coast, and by reliance on a comprehensive inventory method, (120) questionnaires were distributed to all officials in branches The aforementioned commercial banks, and (111) questionnaires were retrieved from them, (4) questionnaires were excluded due to their lack of suitability for statistical analysis, thus the number of retrieved and valid questionnaires for statistical analysis is (107) questionnaires, with a response rate (89.92%).The results showed that the dimensions of human capital are available to a large degree in the banks under study, and with relative importance (79.1%).